1984
DOI: 10.1038/clpt.1984.171
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of amitriptyline and of zimelidine on the sleep electroencephalogram of depressed patients

Abstract: The effects of amitriptyline (n = 14) or zimelidine (n = 13) on the sleep electroencephalogram of hospitalized depressed patients were assessed in a double-blind protocol involving 28 days of active dosing. Zimelidine induced no immediate improvement in sleep continuity, and even after 3 wk on zimelidine subjects tended to have longer sleep latency, more awakenings, and lighter non-rapid eye movement (REM) sleep than before taking the drug. Zimelidine did, however, induce a rapid and persistent alteration of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…This study confirmed an earlier report of the immediate effects of fluvoxamine on sleep in patients with depression (58). Zimelidine also increases the amount of wakefulness during the night and shows REM-suppressing effects in patients with depression (59,28). Conversely, citalopram appeared to suppress REM sleep and increase REM latency without significant deleterious effects on sleep continuity or wakefulness during the night in a study of patients over 6 weeks of treatment (60).…”
Section: Other Ssrissupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirmed an earlier report of the immediate effects of fluvoxamine on sleep in patients with depression (58). Zimelidine also increases the amount of wakefulness during the night and shows REM-suppressing effects in patients with depression (59,28). Conversely, citalopram appeared to suppress REM sleep and increase REM latency without significant deleterious effects on sleep continuity or wakefulness during the night in a study of patients over 6 weeks of treatment (60).…”
Section: Other Ssrissupporting
confidence: 89%
“…Clomipramine and desipramine are 2 ofthe most potent REM-suppressing TCAs, followed by imipramine and nortriptyline (25)(26)(27)(28)(29). Clomipramine, desipramine, and amitriptyline also significantly increase stage I sleep and decrease sleep efficiency over baseline levels (29).…”
Section: Tricyclicsmentioning
confidence: 99%
“…It has been postulated that the anticataplectic action of tricyclics is mediated by REM suppression. In previous studies, short-term administration of large doses of zimelidine produced some degree of REM suppression in animals (24) and in human depressed patients (25). However, in the present study, no REM suppression was seen during nocturnal or diurnal sleep recordings except for the first morning nap.…”
Section: Physiopathology Of Cataplexycontrasting
confidence: 51%
“…administration, there is evidence of tolerance with some measures of REM activity during long-term treatment, particularly in patients [33,36] . However, little is known about the long-term effects on sleep in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%